The site of emotion in Vygotski’s psychology: Historical reflexivity and claim - Rodríguez, Wanda C. (2013)
The purpose of this article is to affirm historic reflexivity as a conceptual and methodological tool in the vindication of the place of activity in Vygotski’s psychology. The cognitive bias that has dominated the interpretation of Vygotski’s works and the sociocultural and institutional context where it was forged is examined. Through the analysis of original texts and cotemporary elaborations, we establish the place of emotions and affects in Vygotski’s theory. We conclude that current cultural and historical transformations have opened the door the consideration of these dimensions, and at the same time warn about the risk of oversimplification that has characterized the uses of other Vygotskian’s ideas, as happened with his concept of zone of proximal development.